Rational designed structured superhydrophobic iron oxide surface towards sustainable anti-corrosion and self-cleaning - He, Shijun (2022)
A hierarchical micro-/nanostructure, consisting of nano-sized Fe2O3 needles vertically grown on the {1 1 1} facets of micro-octahedral Fe3O4 particles, has been successfully prepared on the surface of N80 steel using hydrothermal treatment followed by annealing. The nanoneedles were transformed from nanoparticles on the micro-octahedral facets under the influence of mixed acetone and acetic acid gas atmosphere, and the length of nanoneedles can be controlled by the annealing time. The superhydrophobic Fe2O3/Fe3O4 composite surface with water contact angle (WCA) of 157.3° and sliding angle (SA) of 8.1° was obtained after decorated with stearic acid. The influence of the annealing time on the surface morphology and hydrophobicity was explored and optimized. The superhydrophobic surface displays great self-cleaning and anti-corrosion performances with good mechanical robustness. This method opens a new venue towards preparing micro-nanostructures on the surface of metallic materials for enhanced anti-corrosion and self-cleaning applications.